Cellular response of THP-1 macrophages to polystyrene microplastics exposure. (1st January 2023) - Koner, Shramana; Florance, Ida; Mukherjee, Amitava; Chandrasekaran, Natarajan
Abstract: Microplastic in the environment have the capability to reach the human immune system via the ingestion, inhalation and direct contact. Polystyrene (PS) is one of the most widely used plastics, which is made up by polymerization of styrene monomers. Mounting evidences on the presence of microplastics in blood clearly indicate their access to macrophages that are major component of the immune system. However, data on the response of macrophages to microplastics exposure are limited. Our study reports the response of human macrophages transformed by PMA (phorbol 12-myristrate 13-acetate) to exposure to PSNPs of size range (≤ 450 nm). The polystyrene particles utilized in this study, were formulated from beads to powder by grinding and filtering the particles to acquire a range of size ≤ 450 nm particles with deionized water. This size variation used in this experiment imitates the size of plastic that humans can ingest plastic particles through food that gets fragmented from plastic cups and plates. Here we report that exposure to PSNPs (50–500 µg/mL) significantly decreased the viability of human macrophages. In addition, PSNPs (500 µg/mL) induced oxidative stress and decrease cell proliferation. Exposure to PSNPs decrease the membrane potential of mitochondria and caused damage to the DNA of macrophages. Overall, our study reports the differential toxic effects of PSNPs on human macrophages, delineating the potential risks of PSNPs exposure to human health.